Evaluación de la eficiencia de enraizadores en el incremento de la masa radical del banano (Musa AAA) y su efecto en las poblaciones de nemátodos - Rea Reyes, Jonathan Daniel (2020)
In Ecuador the banana area reaches approximately 180,333 hectares, which are distributed mainly in the provinces of Los Ríos, Guayas, El Oro and Esmeraldas. Annual banana production in Los Ríos province represents 43.23%. These cause root destruction and plant overturning and consequently loss of production. For this reason, this work was carried out with the objective of determining the efficacy of four rooters in increasing the root system of the banana crop, effect on the quality of roots, population density of nematodes and the influence on plant height, pseudostem circumference. and foliar emission. The work was carried out at Hda. Banana Katherine, located at km 16 of the Babahoyo - San Juan road, Los Ríos province. The treatments investigated were the rooters Root Track (1 L / ha), Fertisa Kelp (1 L / ha), Wuxal Ascofol (2 L / ha) and Root Feed (10 kg / ha) compared with an untreated control. The completely randomized block design with five treatments and four repetitions was used. The products were applied to the ground around the sword children. Three evaluations were made at 0, 30 and 60 days after the treatments were applied, in each plot and evaluation a sample of roots and soil composed of five plants of 1.50 to 2.0 m in height was taken. The data evaluated were: total weight of the root mass in holes of 13.5 cm3 / plant, Weight of healthy roots damaged by nematodes and other causes, population density of Radopholus similis, Helicotylenchus multicinctus and Meloidogyne spp in roots and soil and physiological characteristics of the plants. The results showed that the rooters Root Track, Fertisa kelp, Wuxal ascofol and Root feed in the indicated doses, did influence the increase of the root mass of the banana plants compared to the non-applied control, especially the Wuxal Ascofol product. The mentioned rooters did not have any positive effect on the production of healthy roots. The Root Track treatment was the one that presented the best results in reducing the population of R. similis, while Root Feed was the one that reduced the population of H. multicintus the most. The Wuxal Ascofol product was the one that showed the best result in reducing the population of soil nematodes. In pseudostem circumference, the best result was recorded by Root Track, while Root feed presented a higher foliar emission.